2005
DOI: 10.1128/aem.71.1.214-219.2005
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis ofS-Equol from Dihydrodaidzein by a Newly Isolated Anaerobic Human Intestinal Bacterium

Abstract: A newly isolated rod-shaped, gram-negative anaerobic bacterium from human feces, named Julong 732, was found to be capable of metabolizing the isoflavone dihydrodaidzein to S-equol under anaerobic conditions. The metabolite, equol, was identified by using electron impact ionization mass spectrometry, 1 H and 13 C nuclear magnetic resonance spectroscopy, and UV spectral analyses. However, strain Julong 732 was not able to produce equol from daidzein, and tetrahydrodaidzein and dehydroequol, which are most likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
141
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(150 citation statements)
references
References 29 publications
5
141
2
Order By: Relevance
“…The HPLC-PDA data clearly showed that the mono peak was observed at a retention time of 27.3 min with twin UVabsorption spectrum at 228 and 280 nm (Fig. 4A and B), which is consistent with the report of Wang et al ( 19 ). Consequently, the HPLC profile at 280 nm of the purified compound also corresponded with that of com- mercial equol standard (Fig.…”
Section: Resultssupporting
confidence: 79%
“…The HPLC-PDA data clearly showed that the mono peak was observed at a retention time of 27.3 min with twin UVabsorption spectrum at 228 and 280 nm (Fig. 4A and B), which is consistent with the report of Wang et al ( 19 ). Consequently, the HPLC profile at 280 nm of the purified compound also corresponded with that of com- mercial equol standard (Fig.…”
Section: Resultssupporting
confidence: 79%
“…Purported to have the potential to lower the incidence of prostate cancer (37), equol has been shown to arise exclusively as a result of bacterial metabolic processes (38), although only a small percentage of humans harbor the gut bacteria that affect this biotransformation (39). It is important to note that neither equol sulfate nor its methyl ester was listed in any metabolite database, again emphasizing the degree of complexity involving the microbiome that remains to be explored.…”
Section: Sulfation Is Observed As a Prevalent Host Response To Bacterialmentioning
confidence: 99%
“…Lower values of sequence identity were observed for strain HE8 and the equol-forming species Adlercreutzia equolifaciens (90.2%), Eggerthella sp. strain Julong 732 (89.9%) and strain DZE (87.6%) from human feces, Asaccharobacter celatus (90.1%) from rat cecum, and strain Mt1B8 from mouse intestine (88.8%), all of which affiliate within the Coriobacteriaceae (13,16,17,20,21,36). All of these bacterial strains produce equol from daidzein, with the exception of Eggerthella sp.…”
Section: Vol 75 2009 Daidzein and Genistein Conversion 1741mentioning
confidence: 99%